Hormone therapy and fractures in postmenopausal women. (1st October 2022) - Yin, Michael T.; Hoover, Donald R.; Shi, Qiuhu; Tien, Phyllis C.; Cohen, Mardge H.; Kassaye, Seble; Gustafson, Deborah; Adimora, Adaora; Weitzmann, M. Neale; Bolivar, Hector; Warriner, Amy; Bares, Sara H.; et al.
Abstract : Background: Fracture rates have been reported to be higher among older women living with HIV (WLWH) than HIV− women. Hormone therapy with estrogen can reduce vasomotor symptoms (VMS) associated with menopause and prevent fractures. As data are limited on the benefits of hormone therapy use in WLWH, we examined associations of hormone therapy, use and fractures. Methods: A prospective study of 1765 (1350 WLWH and 415 HIV−) postmenopausal Women's Interagency HIV Study (WIHS) participants was performed, including self-reported hormone therapy, use and fracture data from 2003 to 2017. Proportional hazard models determined predictors of new fractures at any site or at typical fragility fracture sites (hip, spine, wrist). Results: At the first postmenopausal visit, the median (IQR) age of WLWH was slightly younger than HIV− women [49.8 (46.4–53) vs. 50.7 (47.5–54), P = 0.0002] and a smaller proportion of WLWH reported presence of VMS (17% vs. 26%, P < 0.0001). A greater proportion of WLWH than HIV− women reported hormone therapy use (8% vs. 4%, P = 0.007) at the first postmenopausal visit. In multivariate analyses, white race and smoking were significant predictors of incident fracture at any site but hormone therapy ( P = 0.69) and HIV status ( P = 0.53) were not. Conclusion: Our study did not find evidence of benefit or harm with regards to fracture outcomes in postmenopausal WLWH receiving hormone therapy. Further research is needed to determine whether hormone therapy has benefits beyond treatment of VMS, such as prevention of adverse aging-associated outcomes.